Cytotoxicity and cellular impact of dinuclear organoiridium DNA intercalators and nucleases with long rigid bridging ligands - Nazif, Mohammad Ali; Alborzinia, Hamed; Kitanovic, Igor; Wölfl, Stefan (Dalton transactions, 2012)
The DNA binding modes and cleavage properties of novel dinuclear Ir(III) polypyridyl (pp) complexes [{(η5-C5Me5)Ir(pp)}2(μ-B)](CF3SO3)4 depend on the lengths of their rigid bridging dipyridinyl ligands B. Mono-intercalation and strong DNA cleavage properties were observed for the dipyrido[2,3-a:2′,3′-c]phenazine (dppz) complexes 1 (B = 4-[(E)-2-(4-pyridinyl)ethenyl]pyridine) and 3 (B = 4-(2-pyridin-4-ylethynyl)pyridine), whose intracationic Ir⋯Ir′ distances are about 13.1 and 13.3 Å, respectively. In contrast, UV/Vis and CD spectra were in accordance with a stable intertwined bis-intercalation mode for pairs of cations of 5 (B = 1,4-di(2-pyridin-4-ylethynyl)benzene), whose much longer Ir⋯Ir′ distance of 20.6 Å allows a stack of five aromatic chromophores to be sandwiched between its effectively parallel dppz ligands. Whereas both 1 and 3 cleaved DNA in the dark, complex 5 exhibited only photoinduced nuclease activity. A significantly higher antiproliferative activity towards MCF-7 breast carcinoma cells was observed for the nucleases 1 and 3, whose IC50 values of 0.61 and 0.49 were much lower than that of 2.2 μM for bis-intercalator 5. Values of 3.8 μM, only slightly higher than that of 5, were recorded for the 5,6-dimethylphenanthroline complexes 4 and 6, whose bridging ligands are identical to those of 3 and 5, respectively. Marked antileukemic activity (IC50 = 6-7 μM) associated with increased levels of reactive oxygen species and apoptosis induction was recorded for both 3 and 5 towards Jurkat cells at concentrations of 5 μM and above. Online studies with a sensor chip system indicated that 5 μM solutions of these complexes invoke a rapid and massive reduction in MCF-7 cell respiration.
Gesehen am 05.09.2018